PERENCANAAN PERKERASAN KAKU (RIGID PAVEMENT) RUAS JALAN KARANGASEM, KECAMATAN TANON KM 5+100 – 8+100 DENGAN METODE PD T–14–2003 - Susila, Abi Baskoro Hemawan; Yuono, Teguh; Sumina, Sumina (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2024)
Tanon District is about 14 Km from the district capital Sragen. The beauty of the Tanon sub-district can be seen from the environment that is still maintained and beautiful, plus the friendliness and wisdom of the local residents. This road is a connecting road between Purwodadi-Gemolong-Tanon-Sidoharjo-Sragen. This road section is an effective route used by heavy vehicles and commercial vehicles from the Sragen area to the Gemolong area because it can shorten the travel time. Therefore on this road section it is necessary to carry out road repairs so that traffic can run well and smoothly. The analysis is carried out in several steps. The first step is to collect CBR (California Bearing Ratio) and LHR (Average Daily Traffic) data. The second step is to calculate the rigid pavement design. After that, the calculation of the thickness of the concrete slab is analyzed using the SNI Pd T-14-2003 method. The results of the calculation analysis for Rigid Pavement Planning for Karangasem Road Section, Tanon District KM 5 + 100 – 8 + 100 Using the PD T – 14 – 2003 method, the calculation results for the subgrade CBR value = 4.5%. The results of the pavement thickness calculation obtained 10 cm thick foundation and 16 cm thick concrete slab. And the calculation of the reinforcement we get longitudinal reinforcement ø9 – 250 mm, transverse reinforcement ø8 – 350 mm, dowel bar spokes ø28 – 450mm, spacing 300mm, length mm, tie bars ø13 – 650 mm, spacing 700 mm